Alzheimer's disease is associated with disordered localization of ganglioside GM1 molecular species in the human dentate gyrus. Issue 23 (17th October 2015) - Hirano-Sakamaki, Wakako; Sugiyama, Eiji; Hayasaka, Takahiro; Ravid, Rivka; Setou, Mitsutoshi; Taki, Takao
Abstract : Alzheimer's disease (AD) is a progressive dementia associated with loss of memory and cognitive dysfunction. In a previous study, we demonstrated a decrease in b‐series gangliosides along with a change in ganglioside molecular species in the hippocampal grey matter of patients with AD. The present study demonstrates the use of imaging mass spectrometry for analyzing the spatial arrangement of ganglioside GM1 (GM1) molecular species in the hippocampus. In AD patients, we found a decrease in the ratio of GM1(d20:1/C18:0) to GM1 d18:1/C18:0) in the outer molecular layer (ML) of the dentate gyrus. Because the outer ML is the region of main input into the hippocampus, our findings may have a direct relationship to the mechanism of dysfunction in AD. Abstract : We performed IMS analysis of ganglioside molecular species in the human hippocampus. We observed a decrease of GM1 molecular species ratio in the outer ML of the DG in AD. The disorder indicates a possible relation to dysfunction in AD.